The Long Run Gender Origins of Entrepreneurship: Evidence from Australia's Convict History - Sefa Awaworyi Churchill; Simon Chang; Russell Smyth; Trong-Anh Trinh (Institute of Labor Economics (IZA), 2024)
This paper extends prior theory linking present-day sex ratios to present-day propensity for entrepreneurship among men backward in time to explore the long-run gender origins of entrepreneurship. We argue that present-day propensity for entrepreneurship among men will be higher in neighbourhoods which had historically high sex ratios. We propose that high sex ratios generate attitudes and behaviours that imprint into cultural norms about gender roles and that vertical transmission within families create hysteresis in the evolution of these gender norms. To empirically test the theory, we employ the transport of convicts to the British colonies of New South Wales and Van Diemen's Land in the eighteenth and nineteenth centuries as a natural experiment to examine the long-run effect of gender norms on entrepreneurship in present-day Australia. We use a representative longitudinal dataset for the Australian population that provides information on the neighbourhood in which the participant lives, which we merge with data on the sex ratio in historical counties from the mid-nineteenth century. We find that men who live in neighbourhoods which had high historical sex ratios have a higher propensity for entrepreneurship. We present evidence consistent with the vertical transmission of gender norms within families being the likely mechanism. Arguments for policies to promote female entrepreneurship are typically couched in terms of gender norms representing a barrier to more women starting their own business. We present evidence consistent with gender norms contributing to gender differences in rates of entrepreneurship by being a spur for higher male entrepreneurship rather than a barrier to female entrepreneurship.
Keywords: I31; J21; J22; N37; O10; Z13; Z18; 330; gender norms; sex ratios; entrepreneurship; Australia